2014
DOI: 10.1111/hel.12109
|View full text |Cite
|
Sign up to set email alerts
|

The Interaction of a Histidine‐Rich Protein Hpn with the Membrane Mimics: Implications for Pathologic Roles of Hpn in Helicobacter pylori

Abstract: The present data indicated that Hpn may take part in the pathological roles of Helicobacter pylori through membrane interactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Secretory proteins such as gingipains from P. gingivalis and Hpn from H. pylori are known to activate cytokine secretion (mainly IL-6 and IL-8). 3941 Similarly, the CD-14 binding protein of S. sanguinis also results in secretion of host cytokines IL-6 and IL-8. 42 Further, the protein SerbB secreted by P. gingivalis modulates host cytoskeleton, thus aiding microbes to enter host tissues.…”
Section: Resultsmentioning
confidence: 99%
“…Secretory proteins such as gingipains from P. gingivalis and Hpn from H. pylori are known to activate cytokine secretion (mainly IL-6 and IL-8). 3941 Similarly, the CD-14 binding protein of S. sanguinis also results in secretion of host cytokines IL-6 and IL-8. 42 Further, the protein SerbB secreted by P. gingivalis modulates host cytoskeleton, thus aiding microbes to enter host tissues.…”
Section: Resultsmentioning
confidence: 99%
“…In solution, Hpn exists predominantly as a 20-mer [ 35 ] and each monomer binds 5 Ni(II) with a K d of 7.1 μM. Purified Hpn can assemble in vitro into amyloid-like fibers, interact with membrane mimics and is cytotoxic to gastric epithelial cell cultures [ 36 ] [ 37 ]. The actual existence of such fibers in H .…”
Section: Introductionmentioning
confidence: 99%
“…Laurdan was successfully used in the study of protein/membrane interactions in systems ranging from solutions to live cells . Bulk spectroscopic analysis of Laurdan emission has also been used for investigation of membrane interactions of several amyloid proteins and peptides, such as amyloid-β peptide, lysozyme, histidine-rich protein, and β 2 -microglubin along with studies on αSN. Specifically, Zhu et al initially reported an increased fluidity of mixed anionic/zwitterionic membranes upon addition of protofibrils and fibrillated αSN .…”
Section: Introductionmentioning
confidence: 99%